Praktiese-ekklesiologie Kerkwees in die 21ste eeu - Dreyer, Wim (HTS Teologiese Studies/ Theological Studies, 2016)
The book proposes a radical transformation of existing church and training models in South African Reformed ecclesial circles. It takes the theological discussion, especially in ecclesiology, to the next level and argues for new ways to express belief in ecclesial practice. The book provides a provocative strategic vision which takes the ecclesial challenges of the twenty-first century seriously. The book will benefit not only theologians in the academy but also church leaders. Firstly, a situational analysis which focuses on the circumstances and social standing of mainstream churches in the twenty-first century, is done. Current difficulties and obstacles are identified. These can be contributed mainly to the secularisation and post-Christian tendencies of the era subsequent to the two world wars. Secondly, the responsible renewal of and much needed amendments to the structures of South African Protestant faith communities in a postmodern, postliberal, postcolonial context are proposed. The authority of scripture and the creeds of these churches are foundational for sensible renewal. The book dialogues with the relevant existing literature as it develops its 'missional' approach to being church in the world today. The investigation is thorough, the argumentation sound and the book makes an original and thought-provoking contribution to the field. The contribution includes biblical perspectives on ecclesial communities, a historical overview of the growth and decline of mainstream churches, insights with regard to the available empirical data, and strategies for the future. The work attests to sound methodology and a strong theoretical foundation. Literature from various parts of the world is utilised, which provides both breadth and depth to the work. The author displays an impressive ability to integrate findings from various fields and disciplines.